A cross sectional study to compare effects of mechanical dilatation and sublingual misoprostol on induction of labor in a tertiary level government hospital - Maru, Laxmi; Thakur, Vibhuti; Lambhate, Kavisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To compare sublingual misoprostol versus mechanical dilatation of the cervix with Foley’ catheter in induction of labor, the need for other method of augmentation of labor like oxytocin infusion, to find out maternal outcome and perinatal outcome and to find out rate of caesarean section in both the groups. Methods: The study was carried out in the department of obstetrics and gynaecology, M.Y. Hospital Indore, on pregnancies with an indication for induction of labor either with mechanical dilatation or with misoprostol. Two groups are made each of 100 cases. One group is induced with Foley’ catheter and other with 25 mcg misoprostol sublingually. Both groups are compared on the basis of age, parity, indication of induction, duration of cervical ripening and delivery, need of oxytocin augmentation. Maternal and foetal outcomes are also compared. Results: Most of the cases in both groups were primigravida, belong to 20-25 year of age group. Most cases were induced for postdatism followed by PIH. Induction delivery interval was short in cases received misoprostol. Also misoprostol group required less oxytocin augmentation, and has significant low rate of caesarean section. There was no significant difference in both cases in terms of maternal and foetal complications. Conclusions: Misoprostol is very safe and effective drug for induction of labour. It has property of collagenous remodelling of cervix along with stimulation of uterine contraction. Hence its induction-delivery interval is short with little requirement of oxytocin augmentation. Rate of failed induction is also low.